2010
DOI: 10.1134/s0006297910090075
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ATP-dependent K+-channel opener on K+-cycle and oxygen consumption in rat liver mitochondria

Abstract: The influence of the K+(ATP)-channel opener diazoxide on the K+ cycle and oxygen consumption has been studied in rat liver mitochondria. It was found that diazoxide activates the K+(ATP)-channel in the range of nanomolar concentrations (50-300 nM, K(1/2) ~ 140 nM), which results in activation of K+/H+ exchange in mitochondria. The latter, in turn, accelerates mitochondrial respiration in respiratory state 2. The contribution of K+(ATP)-channel to the mitochondrial potassium cycle was estimated using the select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
14
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 17 publications
9
14
0
1
Order By: Relevance
“…With liver mitochondria, we not only have shown the activation of mK ATP channel by DZ in the absence of Mg·ATP, but observed high sensitivity of the channel to this opener within nanomolar concentration range. Using indirect methods (polarography and light absorbance to monitor the oxygen consumption and mitochondrial volume changes), we have shown full activation of native liver mK ATP channel elicited by ≤500 nM of DZ [55]. Likewise, with the same methods we observed that channel blockage by glibenclamide and 5-HD did not require the presence of Mg·ATP in isolated liver and brain mitochondria [55,56].…”
Section: Mkatp Channels As the Target Of Diazoxidementioning
confidence: 58%
See 4 more Smart Citations
“…With liver mitochondria, we not only have shown the activation of mK ATP channel by DZ in the absence of Mg·ATP, but observed high sensitivity of the channel to this opener within nanomolar concentration range. Using indirect methods (polarography and light absorbance to monitor the oxygen consumption and mitochondrial volume changes), we have shown full activation of native liver mK ATP channel elicited by ≤500 nM of DZ [55]. Likewise, with the same methods we observed that channel blockage by glibenclamide and 5-HD did not require the presence of Mg·ATP in isolated liver and brain mitochondria [55,56].…”
Section: Mkatp Channels As the Target Of Diazoxidementioning
confidence: 58%
“…Because mitochondrial membrane potential and the uncoupling of the respiratory chain (assessed as RCR ratio) were both dependent on the state 4 oxygen consumption, this allowed us to estimate the share of mK ATP channel in bioenergetic effects of DZ and total potassium transport regardless of the presence of ATP-insensitive component [55,56]. Thus we obtained a reliable appraisal of the share of mK ATP channel in potassium transport and mitochondrial uncoupling by DZ in liver mitochondria [55].…”
Section: Appraisal Of Functional Consequences Of K Atp Channels Openimentioning
confidence: 83%
See 3 more Smart Citations